Pengaruh Kualitas Pasir terhadap Keputusan Pembelian di Pertambangan Pasir Dusun Kalicilik Desa Candirejo - Sherly Amanda Putri; Eko Adi Susilo; Hanik Amaria (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study was conducted with the aim of evaluating the extent to which sand quality influences consumer purchasing decisions in the sand mining area located in Kalicilik Hamlet, Candirejo Village, Blitar Regency. The background of this research is based on the fact that in the construction and development sector, the quality of building materials is a very crucial factor. Sand, as one of the main components in construction, plays a vital role in determining the final outcome of a construction project. Therefore, the quality of the sand used is a primary consideration for consumers in choosing a location or sand seller. This study applies a quantitative approach using a survey method as a data collection technique. Respondents in this study consisted of 74 consumers who actively make purchases at the sand mining location. Data were obtained through the distribution of questionnaires containing questions related to consumer perceptions of sand quality and their decisions in making purchases. The collected data were then analyzed using simple linear regression analysis techniques run with the help of SPSS software. The results of the analysis indicate a highly significant relationship between sand quality and consumer purchasing decisions. This is demonstrated by the coefficient of determination (R²) of 0.540, meaning that 54% of the variation in consumer purchasing decisions can be explained by sand quality. Furthermore, the significance value of 0.000 strengthens this finding, indicating that the relationship is not a coincidence. Therefore, this study concludes that the better the quality of sand offered by the mining company, the higher the likelihood of consumers deciding to purchase. The implication of these results is that businesses in the sand mining sector need to pay special attention to the quality of the products they offer.